A Novel Tablet‐Based Approach for Hearing Screening of the Pediatric Population, 516‐Patient Study. (29th October 2019) - Xiao, Lin; Zou, Bin; Gao, Li; Weng, Meiling; Lando, Matthew; Smith, Ann E.; Barber, Wayne; Yao, Hongbing
Abstract : Objective: Assess a tablet hearing game as a screening instrument for pediatric hearing loss. Methods: All children age 3 to 13 presenting to the ENT clinic of a tertiary hospital clinic over a 3‐month period were eligible for study. Five hundred sixteen were entered by completing the tablet screen with calibrated tablet/headphones. All had full standard audiometry or otoacoustic emission testing to assess hearing status. Tablet game data was analyzed to find the best correlation to the air conduction audiogram. The appropriate pass threshold of the tablet game was established and the statistical accuracy of the tablet game versus the air conduction audio was assessed. Results: The overall rate of hearing loss was 29.7% (153 subjects). Conductive hearing loss predominated and was present in 128 children. The tablet game pure tone average from 500– 4000 Hz correlated best with the air conduction audiogram, and was most predictive of hearing loss. Setting the pass level at 20 dB for the tablet screen prioritized detection of hearing loss, yielding a sensitivity of 91% and corresponding specificity of 73.5% for ages 4 and older. Specificity progressively improved with increasing age and was over 90% for all ages 7 and older. Conclusion: Tablet game audiometry as a screening tool performs well in a controlled setting. Based on these results, it can be considered as a reliable screening method for school‐age children and to monitor resolution of otitis media. Level of Evidence: 4, case series Laryngoscope, 130:2245–2251, 2020